Matlab : an introduction with applications. - Gilat, Amos, ....- (Hoboken : Wiley, 2011)
Now in its fourth edition, MATLAB: An Introduction with Applications is used by more students than any other MATLAB text or reference. This concise book is known for its just-in-time learning approach, giving students the information when they need it. The new edition presents the latest MATLAB functionality gradually and in detail. Equally effective as a freshmen-level text, self-study tool, or course reference, the book is generously illustrated through computer screen shots and step-by-step tutorials, with abundant and motivating applications to problems in mathematics, science, and engineering.